Locking screw augmentation in hypertrophic nonunion of tibia: a novel surgical technique - Gatti, Andrea; Tarantino, Umberto; Gasparini, Monica; Cateni, Marco; Piccirilli, Eleonora; Greggi, Chiara; Gasbarra, Elena (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Nonunion is a common complication in long bone diaphyseal fracture. Hypertrophic nonunion is commonly caused by mechanical instability due to high strain at the fracture site whereas atrophic nonunion is mainly caused by biological impairment. Multiple surgical techniques have been reported to treat hypertrophic nonunion of long bones but there is no consensus about what is the best choice. We present our surgical option in hypertrophic nonunion of lower limb.Methods: We performed a locking cortical screw augmentation technique in fractures previously fixed with plate and screws in order to increase plate stability and to enhance fracture healing process.Results: Radiographic evaluations carried out three months after surgery showed that the fracture line is radiographically filled by bone callus. No pain, no limp, no signs of infection or implant failure were reported.Conclusions: Locking cortical screw augmentation could represent a valid technique to reduce micromovements and to increase the stability at the fracture site with the possibility of early weight bearing and good clinical outcome.